JRII special sonic anemometer study: A first comparison of building wakes measurements with different levels of numerical modelling approaches. (1st January 2021) - Carissimo, B.; Trini Castelli, S.; Tinarelli, G.
Abstract: After the summer 2015 chlorine releases during the Jack Rabbit II field experiment at Dugway Proving Ground, a special sonic anemometer study was carried out in October 2015 and March 2016. The goal was to provide documented wind fields in similar conditions to the actual releases and to study building wakes without risk for the instruments. This study included 30 sonic anemometers that were placed around these "buildings" to best capture the recirculating regions. Building wakes are important for the dispersion of pollutants in cities and around industrial plants and therefore we have selected two time periods during March 2016, in order to present model to model and model to data comparisons. There are four models involved in the comparison ranging from a diagnostic wind model with wake parameterization and Lagrangian particle dispersion and a CFD model with a k-ε turbulence closure and solving the Eulerian dispersion equation. Detailed comparisons are carried out for the wind speed and for the turbulence level. Six virtual releases are added in the simulations to investigate how the wake resolving method can affect the dispersion. For the wind speed comparison, the models give fair to good comparison with the sonic measurements. However, for the turbulence comparison the results clearly show a need for improvement, even for the k-ε closure, which still provides the best results. For the concentrations, for which there is no corresponding measurements, we find that the simulations are much closer than for the turbulence comparison. Graphical abstract: Comparison of wind vectors at 1m height for March 24 at 11:00 (left) and 13:30 (right) for the sonic anemometers (black), a CFD with k-eps turbulence closure : Code_Saturne (blue) and a diagnostic model : PMSS_M (green). The sonic anemometer locations are indicated by red dots at the arrow base. Image 1 Highlights: Wake simulation comparisons with sonic measurements around obstacles, during Jack Rabbit II field experiment. Four models of various complexity and CPU requirements are compared for wind speed, direction and turbulence. Good overall agreement for the wind speed but poor for the turbulence with only CFD with k-e closure with statistics above 50%. Less sensitivity between the models for the simulated concentrations (no corresponding measurements).